Is that an answer to the question? Analyzing the opening turns of physiotherapist-patient interactions - Udvardi Anna (2023)
The dissertation is based on the linguistic-pragmatic analysis of 77 interactions between physiotherapists (PT) and patients during their first meeting. The research aims to explore 1) the characteristics of physiotherapists’ opening questions (OpQ), which initiate the problem presentation phase of the visit, 2) the patterns in patients’ answers (second turn – T2) to those questions, and 3) the relationship between the question-answer pairs. Convenience sampling resulted in the recruitment of 22 PTs (all female) and 77 patients (12 males and 65 females) from a single hospital in Budapest, Hungary. The first visits between the participants were audio recorded. Qualitative methods including the approaches of conversation analysis and linguistic pragmatics were applied to explore the characteristics of the OpQs, of the T2s, and the relationships between them. Additionally, statistical analysis of the OpQ-T2 relations was also conducted, using Pearson’s chi-square tests. The descriptive analysis identified four main categories of OpQs. Furthermore, 6 linguistic features were examined in each of the OpQs. Based on the information content of patients’ answers the inductive analysis resulted in the creation of 7 T2 categories. The results of the qualitative and quantitative analyses show that the examined linguistic features of the OpQs do not provide sufficient explanation for the observed variety in patients’ answers and their seemingly non-cooperative nature. The dissertation argues that the sociocognitive approach (SCA) provides an explanatory framework for the phenomena. The main point of this concept is that patients’ answers are influenced by the egocentric component of communication. In other words, patients’ prior experiences, and information that is important and salient for them all affect the content of their answers.